Perancangan User Interface dan User Experience Aplikasi Reservasi Gedung Olahraga Menggunakan Design Thinking - Posumah, Theresia Mutiara; Setiyawati, Nina (STMIK Banjarbaru, 2024)
The development of indoor sports fields is expanding in Salatiga in tandem with the growth of sports activities among millennials and generation Z. This